1999
DOI: 10.1097/00001756-199909090-00012
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic modulation of cognitive flexibility in problem solving

Abstract: Stress causes impaired performance on tests of creativity. Drugs that block beta-adrenergic receptors improve test performance in patients with test anxiety. Furthermore, catecholamine precursors (L-DOPA) reduce the flexibility of semantic networks. Our study investigated the effect of noradrenergic system modulation on cognitive flexibility in problem solving. Eighteen normal subjects undertook three problem solving tasks (number series, shape manipulation and anagrams) 45 min after propranolol, placebo and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
3
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 21 publications
2
126
3
3
Order By: Relevance
“…However, the results of the present study are consistent with those of many behavioral studies that have demonstrated facilitative effects of positive moods on insight task performance with different affect induction procedures (e.g., watching positive films, giving small gifts, listening to positive music, and generating positive thoughts; Isen et al, 1987;Rowe et al, 2007). In past studies, researchers have also reported that negative moods impair cognitive flexibility, employing different affect induction procedures (e.g., baseline negative mood states; situational stressors; Alexander et al, 2007;Beversdorf et al, 1999;Subramaniam et al, 2009). In addition, in Study 2, we found that the brief viewing of positive images induced greater activity in MPFC, whose activity is known to be enhanced by sustained positive mood states during insight tasks (Subramaniam et al, 2009).…”
Section: Valence Versus Arousal Effectssupporting
confidence: 91%
“…However, the results of the present study are consistent with those of many behavioral studies that have demonstrated facilitative effects of positive moods on insight task performance with different affect induction procedures (e.g., watching positive films, giving small gifts, listening to positive music, and generating positive thoughts; Isen et al, 1987;Rowe et al, 2007). In past studies, researchers have also reported that negative moods impair cognitive flexibility, employing different affect induction procedures (e.g., baseline negative mood states; situational stressors; Alexander et al, 2007;Beversdorf et al, 1999;Subramaniam et al, 2009). In addition, in Study 2, we found that the brief viewing of positive images induced greater activity in MPFC, whose activity is known to be enhanced by sustained positive mood states during insight tasks (Subramaniam et al, 2009).…”
Section: Valence Versus Arousal Effectssupporting
confidence: 91%
“…One study investigated the direct effects of noradrenergic changes during creative problem solving by administering either an agonist (ephedrine) or an antagonist (propranolol) to subjects while they solved each of three cognitive tasks: number series problems, shape rearrangement tasks, and anagram word arrangement tasks. For subjects who were able to solve the problems, response time was lower in the group that received propranolol compared to the groups that received either ephedrine or placebo [37]. An important implication of this study is that the effect of propranolol was seen with the anagram task, and not with the tasks that required less cognitive flexibility.…”
Section: Endogenous and Exogenous Changes In Ne Levels Modulate Creatmentioning
confidence: 68%
“…Understanding the effects of pharmacological manipulation on semantic networks may have implications ranging from language perception (Angwin et al, 2004;Kischka et al, 1996) to problem solving (Beversdorf et al, 1999;Beversdorf et al, 2002;Silver et al, 2004). This may also reveal insight into the impairments exhibited by some patient populations (Arnott et al, 2001).…”
Section: Introductionmentioning
confidence: 99%